Anti-Inflammatory Effect of Red Dragon Fruit (Hylocereus polyrhizus) Peel on Male White Rat - Pazri Yuna; Linda Chiuman; Chrismis Novalinda Ginting (Universitas Airlangga, 2023)
Background: The side effects of synthetic anti-inflammatory drugs have become a known problem in medicine as well as in the general public. These side effects problems drive patients to seek alternatives to common anti-inflammatory drugs, especially natural alternatives. Phytochemicals such as flavonoids, alkaloids, and many different others have been identified as potential anti-inflammatory agents. Red dragon fruit (Hylocereus polyrhizus) is one source of such phytochemicals. Whilst the consumption of the flesh of red dragon fruit is very common, utilization of the peel is very rare and often becomes waste. Objective: This study aimed to explore the potential of red dragon fruit peel as an anti-inflammatory agent. Methods: This experimental study with a control group post-test-only design. This study involved in-vitro (protein denaturation inhibition using bovine serum albumin) and in-vivo (carrageenan-induced inflammation on an air-pouch model on 25 white rats) experiment. Results: This study showed that the red dragon fruit peel extract contains flavonoid, alkaloid, saponin, and tannin compounds. Administration of red dragon fruit peel extract suspension was found to be effective at inhibiting protein denaturation and reducing white blood count in the inflammation exudates, and the effectiveness is increasing along with the dose. Conclusion: It can be concluded that the red dragon fruit peel extract was effective as an anti-inflammatory agent, especially at a higher dose.